(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
This paper is a complete discourse on the advocacy of social justice in context of Western Odisha. It provides matrices of issues and challenges that is faced by western Odisha as far as social justice is concerned. Effort has been made to analyze and introspect the main problems behind getting the social justice in western Odisha and examines to what extent it rendered to achieve justice across the region. It endorses with the possible legal provision underlying by the constitution of India with highlighting basic rights and opportunity and vision for an economic democracy. At the last effective policy analysis proved a greater strategy for availing social justice in the western regions. This paper illustrates that social justice could be achieved through establishing an egalitarian society where socio economic and political security guaranteed to the citizen with better policy forum and effective organizational structure.